KAJIAN PERMEABILITAS BETON MINIM PASIR SEBAGAI BAHAN KONSTRUKSI RESAPAN - Sutarno, Sutarno; Mawardi, Mawardi; Supriyo, Supriyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2015)
With the rapid pace of infra-structure development to be followed by the return of soil water conservation efforts (pikiran rakyat.com & kompac,com). Construction of absorption wells is very effective for improving soil water uptake. Absorption wells construction to be more practical if using Buis Beton. This research is to review of concrete to mix by minimal sand proportions with the addition of fly ash and ijuk fibers, so it has good permeability and good strength. This research used laboratory exsperiments by making specimen samples, the specimen with a mixture of cement, sand, Split, Ijuk fibers and Fly Ash. Variations mixture chosen to do research there are six variations based on the weight ratio, in varying amounts of ; 1 PC: 1PS: 0.5 SRIJK: 0,1FS: 5BP, 1 PC: 1PS: 0.5 SRIJK: 0,1FS: 6BP, 1 PC: 1PS: 0.5 SRIJK: 0,1FS: 7BP, 1 PC : 1PS: 0.5 SRIJK: 0,1FS: 8BP, 1 PC: 1PS: 0.5 SRIJK: 0,1FS: 9BP, and 1 PC: 1PS: 0.5 SRIJK: 0,1FS: 10bp. the results is : The best of mixture is by ratio; 1 PC: 1PS: 0.5 SRIJK: 0,1FS: 5BP, to the Content?s Weight is 1.99 Kg / Lt, and have Compressive Strength 130 Kg / cm3 have permeability values k = 1.21 (medium permeability).